Evolution of the notion of a defect positive guarantee - عبد الصاحب علي مطشر (Journal of Legal Sciences, 2021)
The idea of a common defect of the guarantee has gone through many developments in terms of defining the concept of this defect, starting with civil legislation and passing through the United Nations convention on contracts for the international sale of goods of 1980 (the Vienna agreement) and ending with legislation on consumer protection, and the French judiciary had an important role in developing this idea, so this came. Research to study these developments while clarifying the Iraq law’s position on them and explaining the extent to which Iraqi legislation has reached in taking these developments, as the concept of defect no longer includes the shortage in the price of the sale or what is missed by a valid purpose, but rather expanded this concept to be more comprehensive, which facilitates the imposition of the penalty on the contractor which guarantees this defect.